AT-RISK: AuToimmune disorders and cardiovascular RISK. (3rd October 2022) - Conrad, N; Verbeke, G; Molenberghs, G; Goetschalckx, L; Callender, T; Rahimi, K; Mason, J C; McMurray, J J V; Verbakel, J Y
Abstract: Background: Increased cardiovascular risk has been suggested for selected autoimmune disorders. Yet, for many conditions, evidence is insufficient to design more targeted prevention measures and guide clinical decisions. Methods: We used linked primary and secondary electronic health records from the Clinical Practice Research Datalink (CPRD) to assemble a cohort of individuals newly diagnosed with any of 19 autoimmune disorders between 01/01/2000 and 31/12/2017 and free of cardiovascular disorders (CVD) up to 12 months after diagnosis, and up to five individuals matched on age, sex and socioeconomic status, with follow-up until 30/06/2019. We investigated incidence of nine cardiovascular outcomes and used cox-proportional hazards models to examine differences in patients with and without autoimmune disorders accounting for known cardiovascular risk factors. Findings: We identified 432, 883 individuals with autoimmune disorders and 2, 159, 350 matched controls. Of these, 104, 504 people with and 450, 195 without autoimmune disorders developed incident CVD during a median of 5.3 [interquartile range: 2.6, 9.6] years of follow-up. Patients with one or more autoimmune disorders had higher risk of cardiovascular outcomes: adjusted hazard ratio (HR) [95% confidence interval (CI)] 1.34 [1.31, 1.37]. This relationship held for every individual cardiovascular disorder and increased progressively with the number of autoimmune disorders present. Among autoimmune disorders, those associated with systemic inflammation, such as type I diabetes (2.09 [1.91, 2.28]), systemic sclerosis (2.90 [2.29, 3.67]) and systemic lupus erythematosus (2.21 [1.96, 2.50]) presented with highest overall cardiovascular risk (Figure). Interpretation: Autoimmune disorders are associated with a high risk of developing cardiovascular outcomes. These findings warrant targeted cardiovascular prevention measures for patients with autoimmune disorders and further research into pathophysiological mechanisms underlying these complications. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This project has received funding from the European Union's Horizon 2020 research and innovation programme under the Marie Sklodowska-Curie (grant agreement No 843267) and from the European Society of Cardiology (grant number App000037070).